Green synthesis of a CuO/rGO nanocomposite using a Terminalia arjuna bark extract and its catalytic activity for the purification of water. Issue 4 (25th January 2022) - Kumari, Vanita; Kaushal, Sandeep; Singh, Prit Pal
Abstract : In the present study, biogenic synthesis of a CuO/rGO nanocomposite was carried out successfully using Terminalia arjuna bark extract. Abstract : In the present study, biogenic synthesis of a CuO/rGO nanocomposite was carried out successfully using Terminalia arjuna bark extract. Various analytical methods such as UV-vis, PL, FTIR, XRD, FESEM, EDS, HRTEM and XPS were used for the characterization of the synthesized CuO/rGO nanocomposites. Furthermore, the as-prepared nanocomposite samples were efficaciously utilized for selective removal of Bi 3+ and Cd 2+ ions from aqueous solution. Prior to adsorption investigations, the contact time, initial metal ion concentration, pH, and amount of adsorbent were all tuned. The removal effectiveness of one of the nanocomposites, CG-V for Bi 3+ and Cd 2+ ions from the aqueous system was determined to be 98% and 91%, respectively. The maximum adsorption capacity of the nanocomposite for Bi 3+ and Cd 2+ was found to be 138.8 and 112.4 mg g −1, respectively. The photocatalytic studies revealed that 98% of eriochrome black T (EBT) and 90% of methyl orange (MO) dye were degraded in 80 and 100 min, respectively. Adsorption isotherm analysis and kinetic investigations were also carried out to determine the mechanism and adsorption kinetics which followed pseudo second order. This research is expected to provide insights into the biogenic synthesis of nanocomposites and their applications in environmental remediation.